Allium murat-sonayii (Amaryllidaceae), a new species from Türkiye - Balos, Mehmet Maruf; Sonay, Veysel; Çeçen Cahi̇t; Akan, Hasan (Phytotaxa, 2023)
Allium murat-sonayii Balos, Sonay & C. Çeçen is described as a new species from Elazığ Province, Eastern Türkiye. Diagnostic characteristics, a comprehensive description, photographs and a distribution map are provided. Based on morphological features, it belongs in Allium subgen. Allium sect. Allium. It is similar to A. stearnianum, A. stearnianum subsp. vanense, A. aybukeae, A. gemiciana, A. yamadagensis and A. dictyoprasum, but differs from them by several morphological characters, such as bulblets color, stem length, leaf, umbel shape, perigon colour, outer and inner tepal, anther colour, filaments and ovary.